SUMOylation regulation of ribosome biogenesis: Emerging roles for USP36 - Yang, Yunhan; Li, Yanping; Sears, Rosalie C.; Sun, Xiao-Xin; Dai, Mu-Shui (Frontiers in RNA Research, 2024)
Ribosome biogenesis is essential for cell growth, proliferation, and animal development. Its deregulation leads to various human disorders such as ribosomopathies and cancer. Thus, tight regulation of ribosome biogenesis is crucial for normal cell homeostasis. Emerging evidence suggests that posttranslational modifications such as ubiquitination and SUMOylation play a crucial role in regulating ribosome biogenesis. Our recent studies reveal that USP36, a nucleolar deubiquitinating enzyme (DUB), acts also as a SUMO ligase to regulate nucleolar protein group SUMOylation, thereby being essential for ribosome biogenesis. Here, we provide an overview of the current understanding of the SUMOylation regulation of ribosome biogenesis and discuss the role of USP36 in nucleolar SUMOylation.